A numerical scheme for the prediction of hurricane and typhoon movement - Renard, Robert J. (1967)
The vector motion of severe tropical cyclones (including storm, hurricane/typhoon stages) is forecasted by a numerical scheme which involves two steps: a . Numerical geostrophic steering of the center of the cyclone using the U.S. Navy Fleet Numerical Weather Facility's (FNWF) operationally produced smoothed isobaric height fields, called SR. The tropical perturbations are steered in one-hour time steps up to 72 hours, using winds derived from the SR analysis dated closest to warning time. SR500 mb. in the Pacific and SR 700 mb . in the Atlantic gave the most accurate forecasts on tests of ten northwest Pacific typhoons and all five north Atlantic tropical storms and hurricanes in the period 15 August-1 November 1965. Forecasts were made twice daily, 0600 and 1800 GMT, during this period using best track information. b . Next, the numerical-steering prediction is objectively modified to adjust for bias (i e ., deficiency in both zonal and meridonal motion) by utilizing errors made in the most recent l2- and 24-hour numerical-steering forecasts. Several modes of adjustment are employed; the·most recent 12-(12- and 24-) hour numerical-steering bias yields the most accurate correction of subsequent Atlantic (Pacific) forecasts out to periods of 72 hours. The optimal Naval Postgraduate School (NPGS) technique produces forecast errors ranging from an average of 4.2 knots for 12-hour forecasts to 6.2 knots for 72-hour forecasts. The U .S. Navy 's official forecast accuracy is excelled by the NPGS scheme for all. time periods. Stratification of error statistics by area, trajectory and stage of storm, intercomparison with ESSA 's NHC-64 technique, discussion of merits and deficiencies of the research program relative to operational forecasts and current experiments at FNWF, are discussed. Naval Weather Research Facility, Norfolk, VA